Some Thoughts on the Third Renaissance - A.Abdullazizov (Periodica Journal, 2025)
The author of the article expresses his views and opinions about the Third Renaissance, which is becoming more and more popular in Uzbekistan.
Keywords: The rise of science; art and culture; the Third Renaissance